Relations between the Carpathian Basin and South East Europe during the 10th century. The evidence of the minor objects - Langó, Péter (Dissertationes Archaeologicae, 2013)
Abstract of PhD thesis submitted in 2013 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Csanád Bálint.